Proceeding the 13 th international Asian urbanization conference : Rapi urbanization and sustainable development - Rini Rachmawati (Yogyakarta:Badan Penerbit Fakultas Ekonomi, 2016)
Koleksi Referensi (Tidak Dipinjamkan)